Low-Temperature Performance and Evaluation Index of Gussasphalt for Steel Bridge Decks - Hongyu Ye; Xuancang Wang; Naren Fang; Ziyuan Su (Advances in Materials Science and Engineering)
Gussasphalt is widely used in steel deck pavement in cold regions; thus, it should have good low-temperature performance. A method for evaluating the low-temperature performance of gussasphalt is presented in this paper. Low-temperature bending, bending creep, and splitting tests were used to study the performance of different types of gussasphalt. The sensitivity and correlation between low-temperature indices obtained from three methods were compared and analyzed with sensitivity factors and the grey relational coefficient, respectively, and the low-temperature evaluation index and standard of gussasphalt in cold regions were determined. Flow, penetration at 50°C, low-temperature bending, and bending fatigue tests of the trabeculae were carried out after secondary mixing of gussasphalt asphalt concrete. Degradation of the material performance after different storage times was studied. Finally, taking the strain energy density as the main control index and considering the fluidity, the high-temperature performance, fatigue characteristics, technical requirements for storage, and mixing time of gussasphalt in cold weather after two mixing procedures are discussed.